DNA methylation and its influence on the pathogenesis of osteoarthritis: a systematic literature review - Thomas Nau; Samira Cutts; Nerissa Naidoo (EFORT Open Reviews)
Purpose: Evolving evidence demonstrates the role of epigenetics in the pathogenesis of osteoarthritis (OA), whereas in terms of mechanism, DNA methylation has received the highest attention thus far. This systematic review summarizes the current knowledge of DNA methylation and its influence on the pathogenesis of OA. Methods: A protocol in alignment with the PRISMA guidelines was employed to systematically review eight bibliographic databases between 1 January 2015 and 31 January 2021, to identify associations between DNA methylation and articular chondrocytes in OA. Results: We identified 23 gene-specific studies and 28 genome-wide methylation analyses. Gene-specific studies focused on pro-inflammatory markers in OA, demonstrating that DNA hypomethylation in the promoter region results in overexpression and hypermethylation is linked to gene silencing. Others reported on the association between OA risk genes and DNA methylation. Genome-wide methylation studies reported on differentially methylated regions (DMRs) comparing OA and non-OA chondrocytes. DMRs were seen in hip OA and knee OA chondrocytes. Conclusion: The current body of literature demonstrates the potential and crucial role of DNA methylation in the pathogenesis and progression of OA. This knowledge contributes to the understanding of the pathomechanisms behind OA at gene-specific and genome-wide levels. The observed differences in DNA methylation between healthy and diseased tissues indicate the occurrence of changes in DNA methylation. Based on this, future research in this field that explores the characteristics of potentially reversible changes in DNA methylation may lead to opportunities for causative treatment options for OA.